SWARNAKUMARI MENON : AN INTERVIEW T.K. ANANDI
Smt. Swarnakumari Menon is known to us only as the President of All India Women Conference, Kerala chapter. But in fact she is one of the persons who created history in the freedom movement of our country. Clad in white khadhar with a whiter hair, she has sparkling eyes that are still confident, and she looks like the rising sun even at the age of 78. She stays in the SI. Apartments, Calicut. She has lived all her life for our country, for the freedom of our country. She has all memories of Kasthurbha Amma and Gandhi mahaan who came and stayed in their house during 1930. She stays all alone in the flat, but loneliness is not a problem for she is accompanied by memories of the past. Even now she is disturbed by the political happenings in Kerala and the declining social location of women. She is the President of the All India Women’s’ conference.